Reassessing David S. Powers' Thesis On The Formation of Islamic Inheritance Law - Ahmad Zubairin; Aly Aulia (International Journal of Educational Research & Social Sciences, 2026)
This article critically reassesses the historical-critical thesis of David S. Powers, an American historian of Islamic law at Cornell University, as presented in his influential monograph Studies in Qur'an and Hadith: The Formation of the Islamic Law of Inheritance (1986). Western scholarship on Qur'anic law has long been divided between studies of Muslim exegesis and independent Western reconstructions of Qur'anic themes; Powers' work belongs to the latter and has shaped subsequent debate on the historicity of Islamic inheritance law, yet critical engagement with it from Muslim academic circles, particularly in Indonesia, remains limited. This study addresses that gap through a qualitative library research design, using content analysis combined with a historical-critical approach to Powers' primary text and to recent scholarship on Qur'anic inheritance and Orientalist method. The analysis shows that Powers simultaneously revises two established positions: he rejects Joseph Schacht's thesis that Islamic law only crystallised around 725 CE, arguing instead that Qur'anic legislation on inheritance was operative from the Prophet's lifetime; and he argues that the early Muslim community subsequently altered the reading of the inheritance verses, replacing a flexible, will-based "proto-Islamic" system with the fixed-share doctrine later codified as 'ilm al-fara'id. The discussion further shows that, while methodologically provocative, Powers' reconstruction rests on an unverified assumption of coordinated textual manipulation and an interpretation of Q. 4:12 that is not fully supported by the transmitted asbab al-nuzul, leaving the classical understanding of naskh a stronger explanatory account.